Implementasi Kebijakan Pelayanan Bimbingan Manasik Haji Bagi Lansia pada Kantor Kementerian Agama Kabupaten Karimun - Sufriadi (JURNAL ILMIAH GEMA PERENCANA, 2024)
The aim of this article is to describe the implementation of the Hajj ritual guidance service policy for the elderly at the Karimun Regency Ministry of Religion Office. This article uses a qualitative method, which aims to describe certain circumstances. This discussion focuses on the duties and functions of the Hajj and Umrah Organizing Section of the Karimun Regency Ministry of Religion Office. There are three data collection techniques used, including the interview technique, namely the data collection technique through direct questions and answers with key informants, the observation technique, namely observing objects by writer directly, and the third, document study and literature study techniques. From the study results, data was obtained that the implementation of the hajj ritual guidance service policy at the Karimun Regency Ministry of Religion Office is going well and as a result, regulations for the elderly need to be improved cause not elderly friendly. Thus, it is concluded that the implementation of the Hajj Manasik Guidance Service Policy at the Karimun Regency Ministry of Religion Office is good, only solutions are needed regarding special regulations for the elderly.